2022
DOI: 10.17219/acem/149400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to air pollution on acute cardiovascular and respiratory admissions to the hospital and early mortality at emergency department

Abstract: Żyrek D, Krzemińska A, Żyrek N, et al. Effects of exposure to air pollution on acute cardiovascular and respiratory admissions to the hospital and early mortality at emergency department [published online ahead of print on May 11, 2022].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Prolonged exposure to air pollutants poses a threat to human health and the quality of life [ 1 , 2 ]. Numerous epidemiological studies have demonstrated that exposure to airborne particulate matter (PM) is associated with a significant increase in hospitalization and mortality rates [ 3 , 4 ]. In 2013, the International Agency for Research on Cancer classified PM as a Group 1 carcinogen to humans [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exposure to air pollutants poses a threat to human health and the quality of life [ 1 , 2 ]. Numerous epidemiological studies have demonstrated that exposure to airborne particulate matter (PM) is associated with a significant increase in hospitalization and mortality rates [ 3 , 4 ]. In 2013, the International Agency for Research on Cancer classified PM as a Group 1 carcinogen to humans [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that short-term exposure to air pollutants could cause various adverse health effects in people of different ages, such as respiratory and cardiovascular diseases [ 1 5 ]. Children have immature respiratory development, narrow bronchi, higher lung ventilation rates and lower immune capacity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%